Social Network Analysis and the Dating of Coptic Manuscripts from the Monastery of Saint Macarius - Cook, Samuel Peter (2025)
The present article focuses on the potential of Social Network Analysis (SNA) to assist in dating undated Coptic manuscripts from a monastic context. Focusing on one individual – Papa Mena of the Great Cell, a monk and lector from the Monastery of Saint Macarius in Lower Egypt – I examine the social networks in which he participated in order to estimate the dates of the manuscripts in which he appears. The results of this analysis have further implications for our understanding of manuscript production and donation in Islamic Egypt, as well as demonstrating the usefulness of SNA in the study of early Christian manuscripts.
Keywords: Network Analysis; Monastery of Saint Macarius; Egyptian Monasticism; Coptic manuscripts